Gugatan Atas Eksistensi Agama di Ruang Publik - Mohammad Yusuf Zakaria; Muhammad Sandi Kurniawan; Mohamad Nur Rosyid; Slamet Muliono Redjosari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Two Jakarta residents filed a lawsuit with the Constitutional Court of the Republic of Indonesia demanding the right to live without religion. They blamed the biodata on the KTP. They intend for the religion column on their KTP not to be filled in or left blank. They admit that they do not adhere to religions and beliefs that are recognized in Indonesia. On the grounds that they experience loss of constitutional rights because they have to fill in the religion column. They submitted a request for material review of article 61 paragraph (1) and article 64 paragraph (1) of Law Number 23 of 2006 concerning population administration (UU Adminduk) regarding population biodata. As well as discussing the implications for the protection of human rights. The decision being challenged relates to the interpretation of the constitution regarding freedom of religion and belief, as well as other civil rights that are considered ignored or limited. This study uses a normative juridical approach by studying statutory regulations, Constitutional Court decisions, and relevant legal doctrines. Apart from that, this study also involves a human rights perspective to see how courts consider the balance between public interests and individual rights. The aim of this study is to show that this lawsuit highlights the existence of gaps in the protection of fundamental constitutional rights, especially regarding the right to live without being forced to believe in certain beliefs.